The Effect of Adding Degreased Flaxseeds on the Quality of Pork Sausages - Tomasz Florowski; Anna Florowska; Daria Wodzyńska; Marta Chmiel; Lech Adamczak; Dorota Pietrzak (Biology and Life Sciences Forum, 2025)
The aim of the study was to assess the effect of adding degreased flax seeds (DFS; 2%, 4%, 6%, and 8%) on the quality of homogenized pork sausages. It was found that the 2% DFS addition to the batter had no effect on most of the analyzed quality parameters of sausages (i.e., cooking and reheating loss, water activity, pH, L* and a* color parameters, water, protein and fat content, shear and compression force, elasticity, and meat taste). However, a 2% DFS addition resulted in an increase b* color parameter, reduction in the intensity of the meat odor, and the appearance of the odor and taste of flax seeds in the product, as well as a slight deterioration in its overall desirability. The higher the DFS addition, the more pronounced its adverse effect on the product quality, especially its sensory quality. A large addition of DFS to the batter also caused a significant reduction in the shear force of sausages, a reduction in the L* and a* color parameters, and an increase in the pH value.